Financial Technology Lending and Consumptive Attitude on Student Lifestyle - Imam Sopingi; Lailatul Maghfiroh Putri Rifardi; Athi’ Hidayati (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2024)
The background of the problem in this study is the increasing use of financial technology (FinTech) lending among students accompanied by changes in consumptive attitudes, which have an impact on their lifestyle. The purpose of this study is to analyse the influence of FinTech lending and consumptive attitudes on students' lifestyles. This research uses a quantitative method with a survey approach to students from various universities in Jombang. A total of 200 respondents were selected through purposive sampling technique, namely those who have used FinTech lending. The data was analysed using multiple linear regression to determine the effect of independent variables on the dependent variable. The results showed that partially and simultaneously, both independent variables, namely FinTech lending and consumptive attitude, have a significant influence on students' lifestyle. The implications of this study emphasise the importance of students' awareness of the impact of using FinTech lending and their consumptive attitude. Higher education managers and FinTech service providers are expected to improve financial literacy among students to help them manage their finances more wisely.